Penggunaan Media Powerpoint Untuk Meningkatkan Hasil Belajar Simbol Sila-sila Pancasila Siswa Kelas 1 Sekolah Dasar Negeri 3 Sawahan - Enda Setio Rini; Sukron Dzazilan; Maratus Solicha (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
Based on observations on October 8, 2020 at SD Negeri 3 Sawahan, Turen Subdistrict, Malang Regency, on Thursday during learning what is less attractive online, students are less active in online learning activities, teachers do not use media for classroom learning, students do not pay attention to teacher explanations, in delivering material they only read so students joke and chat on their own, and learning uses lecture and question and answer methods only . Meanwhile, the observation data regarding the minimum completeness standard score that must be met by students must be able to obtain a score ≥ 70 which is determined in SD Negeri 3 Sawahan, Turen District Malang. Of the 8 total grade 1 students who took the daily test, there were 2 students who had finished learning and 5 students had not finished so they had to take remedies to reach the specified KKM. The aim of the research is to know and describe the learning of using Powerpoint Media to improve the learning outcomes of the Principle of Pancasila Symbols for Grade 1 Students of SD Negeri 3 Sawahan, Turen District, Malang Regency This research method is Classroom Action Research which consists of Pre Cycle, Cycle 1 and, Cycle 2. Each cycle consists of planning, implementing action, observing, and reflecting. The results in the pre-cycle showed that the average score of the individual student tests carried out at the end of the lesson was still low, namely 66.2. The percentage of completeness in pre-cycle learning is only 25%, based on the completeness criteria, this means that students' learning completeness is lacking. In Cycle 1, there was an increase in the average individual student learning outcomes from 66.2 to 71.2 with a completeness percentage of 37.5%. The increase in the average score of students is due to this cycle the students look enthusiastic and interested in the Powerpoint learning media used. In cycle 2 shows an increase in the average value of student learning outcomes from 71.3 in the first cycle to 93.8 with an increase in the percentage of student completeness in cycle II to 87.5% and is included in the criteria for student completeness as very good and declared successful.